Grupo de simetria ao quadrado mágico: contribuição para aprendizagem dos alunos do 9º ano do ensino fundamental - Ferreira, Dirlei Corrêa (Brasil, 2019)
The Magic Square has a long history and provides a playful way to develop logical thinking among students. On the other hand, Group Theory is abstract but has concrete manifestations in the magic square theory, such as the square symmetry group. This paper aims to introduce the concepts of Symmetry Group in basic education through the Magic Square. Thus, we analyze the magic square and its contribution to develop students' logical reasoning and some basic aspects of group theory. This work was developed with students of the 9th grade of Elementary School of Prefect Alexandre Montoril State School. A qualitative and quantitative field research was carried out, in which the students' evolution in the cognitive aspect in relation to the applied content was descriptively evaluated. Two questionnaires were applied, one initial to evaluate the students' knowledge regarding the content, and another after applying the work to identify the research results. Finally, there were improvements regarding the participation and performance of students in the activities performed from a different methodological approach through the Magic Square.